2023
DOI: 10.1038/s41598-023-31147-0
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and coping behaviour among adolescents in a high-income city-state during the COVID-19 pandemic

Abstract: The study aimed to determine the resilience of multi-ethnic, multi-cultural adolescent students in cosmopolitan Singapore, their coping abilities, and the impact on their social and physical activities during the COVID-19 pandemic and its association with their resilience. A total of 582 adolescents in post-secondary education institutes completed an online survey from June to November 2021. The survey assessed their sociodemographic status, resilience level using the Brief Resilience Scale (BRS) and Hardy-Gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Similar results were reported in a multicultural community study of adolescents in Singapore, where it was found that, despite the pandemic, about 50 per cent of the adolescents under study presented an average level of resilience, rather than a lower one, as it was assumed. Lower levels of resilience were specifically associated with poorer coping skills and lower socio-economic status, which in Singapore is the case of the minority of young people of Chinese origin ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were reported in a multicultural community study of adolescents in Singapore, where it was found that, despite the pandemic, about 50 per cent of the adolescents under study presented an average level of resilience, rather than a lower one, as it was assumed. Lower levels of resilience were specifically associated with poorer coping skills and lower socio-economic status, which in Singapore is the case of the minority of young people of Chinese origin ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical terms, this is an indicator of a reduced sense of security, which is lower in adolescents aged 14 and 15. This is perhaps the result of emotional imbalance increasing with age, therefore there is a developmentally justified search for security in the relationship with parents ( 45 , 48 ). However, it cannot be excluded, either, that adolescents express their concern with tragic events and with this infrequent developmental burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation